Portrait des minorités de langue officielle au Canada : les anglophones du Québec - Corbeil, Jean-Pierre; Chavez, Brigitte; Pereira, Daniel (Statistique Canada, 2010)

Portrait of Official-Language Minorities in Canada: Anglophones in Quebec - Corbeil, Jean-Pierre; Chavez, Brigitte; Pereira, Daniel (Statistics Canada, 2010)

Seeking social services on the Gaspé coast: A narrative analysis of Anglophones’ experiences of access and care [master's thesis, University of Victoria] - Finlayson, S. (University of Victoria, 2017)
This research addresses the concern that Anglophone populations in the predominantly French speaking Gaspé region of eastern Québec are experiencing high rates of social problems such as poverty and unemployment. Anglophones in this region, as in other rural regions of Québec, have identified facing difficulties related to access to social services, an aspect which further complicates existing social problems. Using a narrative methodology and post structural, feminist and intersectional lenses, this research explores the experiences of English speaking service users in accessing and engaging with social services on the Gaspé coast. This study also explores the boundaries and reproduction of linguistic categories and identity and offers insight into resisting dominant discourses pertaining to linguistic difference in Québec, specifically within the context of social services. The results of this research demonstrate that service users’ experiences were characterised by disproportionately negative effects in regards to service access and delivery such as intensified logistical problems and social work practice related weaknesses. The research also concludes that experiences involved multiple, intersecting problems, which were irreducible to the singular dimension of language. The intersections of language and race, language and class, and language and ability were raised as critical concerns in terms of access to social services on the Gaspé coast. Finally, the encounters between Anglophones and Francophones in the context of health and social services in the region were found to be entangled and inseparable from the historical and ongoing political struggles over language on this territory.

Perceived importance of native language use in service encounters - Holmqvist, Jonas; Van Vaerenbergh, Yves (The Service Industries Journal, 2013)
Despite the importance of interactions in services, the role language plays in services is an under-researched field. This paper outlines for which services language is especially important. Consistent across studies in three countries (Belgium, Canada and Finland), the findings suggest that bilingual consumers find it particularly important to be served in their native language in high-involvement services. Moreover, for high-involvement services, all consumers find it important to be served in their native language. For low-involvement services, elderly consumers are less willing to switch language than young consumers. The importance of native language use did not differ between males and females.

English-language health and social services access in Québec. Baseline data report 2015-2016 - Pocock, Joanne (Community Health and Social Services Network, 2016)

Accès interrégional aux services sociaux et de santé pour les personnes d’expression anglaise de l’est de Québec - Richardson, Mary; Gagnon, Hélène (Committee for Anglophone Social Action et Partenaires communautaires Jeffery Hale, 2015)
Cette étude visait à mieux comprendre ce que vivent les anglophones des régions de l‘est du Québec qui doivent se déplacer vers des centres urbains pour recevoir des services de santé spécialisés.

Enjeux des services sociaux et de santé en contexte bilingue ou multilingue national. Revue de littérature - van Kemenade, Solange; Forest, Mariève (Secrétariat national du Consortium national de formation en santé, 2015)